Comparative Efficacy of Canine Parvovirus-2 Infection Diagnostic Tests Commonly Prevailing in India - Dorlikar, PR; Warke, SR; Tumlam, UM; Ingle, VC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Early and rapid field diagnosis of CPV-2 infection is essential for preventing disease transmission from infected to susceptible dogs. In the present study total 91 fecal samples and rectal swabs collected from a diarrheic and non-diarrheic dog from clinics located in and around Nagpur. Polymerase Chain Reaction, Rapid Antigen detection kit, and Hemagglutination test (HA) were able to detect CPV-2 in 41 (45.05%), 34 (37.36%) and 22 (24.17%) samples, respectively. The evaluation revealed that the PCR method was found to be most sensitive followed by antigen detection kit and HA field test. Sensitivity and specificity of antigen detection kit with respect to PCR method were found to be 78.08% and 96.00%, respectively. The finding suggests PCR with the highest sensitivity may be taken as a gold standard test of CPV-2 relative to other diagnostic tests. HA test could be employed for the preliminary screening in field because of its rapid response and low cost.